التحديات التربوية لروضة الأطفال "تاديكا" في جنوب تايلاند : The Challenges Kindergarten "Tadika" in southern Thailand to study Islamic education - Yasingo, Ikram; Ahmad H. Osman, Rahmah; Mohammed, Fadalla Abd Elgleil (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص روضة الأطفال أو ما يطلق عليها في اللغة الملايوية "تاديكا" .. مؤسسة تعليمية في المجتمع الإسلامي في أرخبيل الملايو وكذلك في فطاني. والهدف من إنشائها هو غرس المبادئ الدينية الأساسية. حيث تعمل على جعل الأطفال مسلمين صالحين في المجتمع, إذا كنا نريد الشباب أناسا طيبين ، ويتمتعون بأخلاق حسنة، وعندما يكبرون ويصبحوا بالغين يكونون صالحين في المجتمع ، فلا بد من رعايتهم في الصغر، إذا فعلنا هذا سيكون هناك أناس طيبون ، وسيكون المجتمع صالحًا, لكن في الوضع الحالي ، لقد انخفض عدد الطلاب في التدريس في روضة الأطفال "تاديكا" بشكل كبير بسبب نظرة الآباء لأطفالهم حيث يعتبر البعض ذلك إضاعة للوقت في تاديكا. لأن الدراسة في المدارس الحكومية التايلاندية كافية، وهذا هو السبب في أن بعض الناس في فطاني أكثر بعدًا وغير مهتمين بالدين، إن عدم إرسال الآباء أولادهم للدراسة في "تاديكا" هو أحد العوامل التي تجعل بعضا من المجتمع الإسلامي في فطاني بعيداً عن عقيدة الإسلام. تحاول الدراسة الحالية تحليل الأسباب الرئيسية لعدم إرسال بعض أولياء الأمور أطفالهم إلى مدرسة "تاديكا" وتاريخ "تاديكا" في فطاني. Abstract Tadika is an institution in the Islamic community. The goal is to inculcate basic religious principles. Make children become good Muslims Be a good member of society If young people are good people, have morals and ethics, and when they grow up to be adults, they will be good people in society, there will be good people and society will be good, but in the present situation, the number of students in learning has decreased In Tadika it is steadily due to parents neglecting their children to waste time studying in Tadika. Because studying in Thai government schools is enough that is why people in Pattani are more distant and not interested in religion because not sending them to study Tadika is one of the factors that make the Muslim community in Pattani away from the faith of Islam. The current study attempts to analyze the main reasons why people do not send their children to Tadika School and the history of Tadika in Pattani.